Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 1 - Section 1.8 - Simplifying Expressions - Exercise Set: 47

Answer

$\dfrac{1}{3}(7y-1)+\dfrac{1}{6}(4y+7)=3y+\dfrac{5}{6}$

Work Step by Step

$\dfrac{1}{3}(7y-1)+\dfrac{1}{6}(4y+7)$ Multiply the fractions by every term inside its respective parentheses: $\dfrac{1}{3}(7y-1)+\dfrac{1}{6}(4y+7)=\dfrac{7}{3}y-\dfrac{1}{3}+\dfrac{4}{6}y+\dfrac{7}{6}=...$ Simplify the resulting fractions if possible: $...=\dfrac{7}{3}y-\dfrac{1}{3}+\dfrac{2}{3}y+\dfrac{7}{6}=...$ Continue simplifying: $...=\dfrac{9}{3}y+\dfrac{21-6}{18}=\dfrac{9}{3}y+\dfrac{15}{18}=\dfrac{9}{3}y+\dfrac{5}{6}=3y+\dfrac{5}{6}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.